A Highly Integrated Single-Chip Baseband IC for 2.5th Generation Multimedia Oriented Mobile Phones - Huemer, Mario; Lüftner, Thomas; Weigel, Robert; Hagelauer, Richard; Hausner, Josef (Elektrotechnik und Informationstechnik, 2002)
In this paper we report on the design and architecture of a single chip baseband processor IC for GSM/GPRS/EDGE cellular phone applications. S-GOLD is a mixed signal IC containing all analog and digital baseband functionality of a cellular radio. It is designed as a single chip solution, integrating the digital and mixed signal portions of the baseband in a leading edge 0.13 µm 1.5 V CMOS technology to meet the ever increasing demands of the GSM cellular subscriber market for feature rich and high performance terminals at low costs.
elib2cris::1512001600,huemer2002a
Keywords: mobile; Chip